The Munin Conference on Scholarly Publishing: The short history - Longva, Leif (Ravnetrykk, 2020)
The series of annual Munin Conferences was born in 2006. This is a short history of how it happened, and how the conference has developed over the years, step by step, into one of the most important conferences in Europe within its scope. Scholarly publishing is an important part of, and a prerequisite for progress in research. The advent of the Internet has given options for dramatic changes in the process of publishing and the dissemination of research. This has given the Munin Conferences ample issues to debate over the years, and, most likely, the years to come.